2016
DOI: 10.3390/molecules21091245
|View full text |Cite
|
Sign up to set email alerts
|

On the Effect of Microwave Energy on Lipase-Catalyzed Polycondensation Reactions

Abstract: Abstract:Microwave energy (MWe) is, nowadays, widely used as a clean synthesis tool to improve several chemical reactions, such as drug molecule synthesis, carbohydrate conversion and biomass pyrolysis. On the other hand, its exploitation in enzymatic reactions has only been fleetingly investigated and, hence, further study of MWe is required to reach a precise understanding of its potential in this field. Starting from the authors' experience in clean synthesis and biocatalyzed reactions, this study sheds lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…For example, microwave energy (MWe) has been used as a cleaning synthetic tool to improve enzymatic polycondensation reactions and pre-polymer formation similar to conventional heating, while bulk phase polycondensations under intense microwave irradiation can quickly deactivate the enzyme. 34 Poly(u-pentadecalactone) has been prepared in a pressurized variable-volume view reactor using various solvents. 35 Microreactor based continuous ow chemistry is a green reaction with many advantages such as improved energy efficiency, reaction speed, yield, safety, reliability, scalability, and on-site/on-demand production.…”
Section: Exploration Of Green Reaction Conditionsmentioning
confidence: 99%
“…For example, microwave energy (MWe) has been used as a cleaning synthetic tool to improve enzymatic polycondensation reactions and pre-polymer formation similar to conventional heating, while bulk phase polycondensations under intense microwave irradiation can quickly deactivate the enzyme. 34 Poly(u-pentadecalactone) has been prepared in a pressurized variable-volume view reactor using various solvents. 35 Microreactor based continuous ow chemistry is a green reaction with many advantages such as improved energy efficiency, reaction speed, yield, safety, reliability, scalability, and on-site/on-demand production.…”
Section: Exploration Of Green Reaction Conditionsmentioning
confidence: 99%
“…A number of studies at laboratory [47][48][49] or pilot scale [50] have demonstrated the feasibility of enzymatic polycondensation and ring opening polymerization. As an example, the synthesis of aliphatic polyesters carrying vinyl functionalities [51][52][53] or hydroxyl groups [54,55] has been performed via enzymatic catalysis at temperatures of 50-70 C. Such mild conditions prevent the undesirable cross-reactivity of the polymeric chains observed in traditional chemical polycondensations, carried out at temperatures above 150 C. Moreover, enzymes can be exploited when a mild and limited surface functionalization of polymers is needed.…”
Section: Biocatalysis For Valorization Of Bio-based Building Blocks: ...mentioning
confidence: 99%
“…[262] On the contrary,t he transesterification of b-ketoesters by N435 under microwave irradiationi ns olvent-free conditions gave good results. [267] Finally,t od ate, the enzyme-catalyzed synthesis of polyesters by microwave irradiation have not shown significant improvements. The combination of N435 and microwavei rradiation for the ROP of e-caprolactone did not lead to as ignificant improvement, relative to that of am ore classical heating system.…”
Section: Microwave-assisted Polymerizationmentioning
confidence: 99%
“…[266] Recently,t he transesterification of dimethyl succinate or di- www.chemsuschem.org methyl adipatewith 1,4-BDOinthe bulk or in diethyl ether catalyzed by N435 exhibited similar or lower molar massesw ith microwave irradiation than those with conventionalh eating. [267] Finally,t od ate, the enzyme-catalyzed synthesis of polyesters by microwave irradiation have not shown significant improvements.…”
Section: Microwave-assisted Polymerizationmentioning
confidence: 99%